EFEKTIVITAS PEMAKAIAN E-MONEY DALAM MENDUKUNG SISTEM PEMBAYARAN DI ERA DIGITAL - Tarisya Alfadhilla; Humam Hadi; M. Ilyas Teguh Pratama; Diwayana Putri Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
With the development of technology, significant changes can be seen in payment instruments that provide flexibility and efficiency in every electronic transaction. The use of e-money provides many conveniences for consumers and can also find out the impact of Bank Indonesia's policies on the application of e-money. This study is descriptive qualitative with literature method through literature studies sourced from journals of previous research results. The effectiveness of the use of APMK has a significant positive effect. The use of debit cards has increased every year. But in contrast to credit cards, there is an increase and decrease in card users every year. Merchants in the e-money system that provide payment service facilities with e-money in their payment transactions so that effectiveness. E-money consumers are people who use e-money in their payment transactions. The use of e-money payments increases people's income through decreased transaction costs.